2016
DOI: 10.1016/j.sdj.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of managing avulsed tooth among general dental practitioners in Malaysia

Abstract: Trauma prevention and further education regarding the management of avulsed tooth is an essential requirement to improve general dental practitioners knowledge and clinical skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(42 citation statements)
references
References 15 publications
1
39
1
1
Order By: Relevance
“…The mean value of correct answers in the avulsion trauma management was always lower than the score reported for other dental trauma (crown and root fractures). The results of the current survey are in accordance to those represented in Table 5 [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The mean value of correct answers in the avulsion trauma management was always lower than the score reported for other dental trauma (crown and root fractures). The results of the current survey are in accordance to those represented in Table 5 [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 84%
“…The reported scores by Abdullah et al were the highest [16] compared to the scores reported by Zadik [17] and Hartmann [18], with an average correct response rate of 61.5% and 60.2%, respectively.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…When asked whether the avulsed permanent tooth can be replanted, only 24.9% of dental assistants could give the correct answer 69 . However, the studies done with dentists or specialists reported correct answers in >80% of participants 59,63,66,67,72–74 . Regarding the replantation of avulsed primary teeth, >75% dentists gave the correct response in three studies, 59,63,72 50%‐75% in three studies, 60,61,69 25%‐50% in three studies 62,65,73 and <25% in one study 64 .…”
Section: Resultsmentioning
confidence: 99%
“…Para la particularidad del trauma tipo avulsión, más de la mitad de los estudiantes no asumirían la mejor actitud en caso de tener que atenderlo, lo cual coincide con lo expuesto por Fujita et al [35] en el 2014 (Japón) a partir de estudiantes de Odontología. Otros autores como Abdullah et al [36], en el 2016 (Malasia), reportan cómo, pese a que 46% de los odontólogos generales valorados obtuvo puntajes favorables en la atención de dientes avulsionados, no son resultados totalmente satisfactorios, por lo que sugirieron la mejora tanto del conocimiento como del ejercicio de la práctica clínica. Así mismo, los autores del presente estudio recomiendan que es necesario utilizar algunas estrategias educativas complementarias que permitan capacitar a los estudiantes para mejorar las actitudes ante la atención de estas situaciones clínicas.…”
Section: Discussionunclassified